Pembuatan Asam Asetilsalisilat dari Asam Salisilat dan Asetat anhidrat Menggunakan Proses Sintesis Kalsium Oksida Dengan Reaktor Sebagai Alat Utama - Simbolon, Devi Veronika; Yuniningsih, Susy; Ma'sum, Zuhdi (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Acetylsalicylic acid is a corrosive that relieves pain and lessens discomfort. Sometimes people refer to acetylsalicylic acid as a headache medication. In addition to calcium oxide acting as a supporting specialist and corrosive killing specialist, the dynamic element of acetylsalicylic corrosive is called acetylsalicylic corrosive, which is an engineered subordinate of the compound salicin. It responds with anhydrous acidic corrosive and salicylic corrosive in a stoichiometric proportion. When calcium oxide (CaO) is used, the yield of acetylsalicylic acid is nearly 100% (the maximum amount of free salicylic acid is 2%), and calcium acetic acid is produced. It is a one-pot, exothermic, rapid, and contamination-free reaction. Acetylsalicylic corrosive is produced by mixing acidic anhydrous and salicylic corrosive with calcium oxide. The Short Cylinder That Rises 98% of the chemicals used in the filtering process are acetylsalicylic acids in the evaporator. The main device used is the reactor. The reactor can think acetylsalicylic corrosive while operating at 70°C and 1 atm. The reactor's memorised limit is 331.3031 kg/hour. Financial evaluation findings ROIbt (return on venture) = 48%, ROIat (return on investment) = 43%, Pay Out Season = 1.78 years, BEP (return on original investment) = 31.93%, SDP (shut down point) = 14.74%, and IRR (internal rate of return) = 20.93%. Abstrak Asam asetilsalisilat bersifat asam yang mengurangi rasa sakit dan mengurangi ketidaknyamanan. Selain kalsium oksida yang berperan sebagai zat pendukung dan zat pembunuh asam, unsur dinamis asam asetilsalisilat disebut asam asetilsalisilat, yang merupakan turunan rekayasa dari senyawa salisin, merespons dengan asam asam anhidrat dan asam salisilat dalam proporsi stoikiometri. Ketika kalsium oksida (CaO) digunakan, hasil asam asetilsalisilat hampir 100% (jumlah maksimum asam salisilat bebas adalah 2%), dan kalsium asam asetat dihasilkan. Ini adalah reaksi satu pot, eksotermik, cepat, dan bebas kontaminasi. Asam asetilsalisilat diproduksi dengan mencampurkan asam anhidrat dan asam salisilat dengan kalsium oksida. Silinder Pendek Yang Naik 98% bahan kimia yang digunakan dalam proses penyaringan adalah asam asetilsalisilat di evaporator. Alat utama yang digunakan adalah reaktor. Reaktor dapat berpikir asetilsalisilat asam saat beroperasi pada 70°C dan 1 atm. Batas hafalan reaktor adalah 331,3031 kg/jam. Temuan evaluasi keuangan ROIbt (return on venture) = 48%, ROIat (return on investment) = 43%, Pay Out Season = 1,78 tahun, BEP (return on original investment) = 31,93%, SDP (shut down point) = 14,74% , dan IRR (tingkat pengembalian internal) = 20,93%.